Detection of Rational Speculative Bubbles in the Malaysian Stock Market - Mokhtar, Suraya Hanim (2006)
The general purpose of the study is to investigate the existence of rational speculative bubbles in the Malaysian stock market. A bubble is defined as the asset price movement that is unexplainable by the fundamental (Garber, 1990). Meanwhile, rational speculative bubbles can be defined as an attempt to identify the behavior of investors who act irrationally (Cuthbertson, 1996). Specifically, the study aims to detect the rational speculative bubbles over the period for before (1 994- 1996), during (1 997-1 998) and after the Asian financial crisis (1999-2003). This study provides a modest attempt to investigate the price behavior of stocks fiom a behavioral finance perspective. In theory, the bubble is a theoretically appealing; however the fundamental fails to identify the growth or size of the share prices. This study used abnormal monthly real return of Kuala Lumpur Composite Index and Sectoral Indices (Finance Index, Consumer Product Index, Property Index, Trading and Services Index, Plantation Index, Construction Index and Industrial Product Index) from 1994 until 2003. Statistical analysis used in this study is Duration Dependence Test using the Log Logistic Hazard Model and the Weibull Hazard Model. The empirical findings of the study for both models: (1) Log Logistic Hazard Model and: (2) Weibull Hazard Model revealed the existence of rational speculative bubbles in the Malaysian stock market for before (1994-1996) and after (1999-2003) the Asian financial crisis 1997. In general, the pattern of the bubble behavior for before and after the Asian financial crisis 1997 on Composite Index and Sectoral Indices replicate similar findings in which the bubbles' sizes are huge in 1995. The practical issue suggests from this scenario, the policy makers have to react approximately two years before crisis. Furthermore, the findings illustrate that the bubbles developed over time and explode during crisis. Moreover, investor tends to overact or exaggerate and implies that price movement contains bubbles, apart from the normal white noise. This study presents a number of practical implications to academicians, investors and most importantly to policy makers. Prior to the investigation, there is no published evidence on the detection of rational speculative bubble in the Malaysian stock market especially for the year of 1994 until 2003, therefore this study provides a significant contribution to the body of knowledge particularly in emerging market. The existence of rational speculative bubble in the market lead to better decisions for investors and policy makers on how to minimize risk subsequently, as time goes, market efficiency improves.